2021
DOI: 10.1017/s0033291721004566
|View full text |Cite
|
Sign up to set email alerts
|

The importance of social activity to risk of major depression in older adults

Abstract: Background Several social determinants of health (SDoH) have been associated with the onset of major depressive disorder (MDD). However, prior studies largely focused on individual SDoH and thus less is known about the relative importance (RI) of SDoH variables, especially in older adults. Given that risk factors for MDD may differ across the lifespan, we aimed to identify the SDoH that was most strongly related to newly diagnosed MDD in a cohort of older adults. Methods We used self-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
(66 reference statements)
1
5
0
Order By: Relevance
“…No previous study has examined these associations using longitudinal data. However, our findings on the associations between some types of social relationship satisfaction and individual chronic conditions (eg, depression, hypertension, cardiovascular disease and cancer) are similar to those observed in previous research 10–12 21 32 33. Further research is needed to explore other dimension-specific effects of social relationships on multimorbidity, such as the qualitative dimension (eg, intimacy), structure dimension (eg, quantity) and function dimension (eg, emotional and practical support), which were not addressed in this study.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…No previous study has examined these associations using longitudinal data. However, our findings on the associations between some types of social relationship satisfaction and individual chronic conditions (eg, depression, hypertension, cardiovascular disease and cancer) are similar to those observed in previous research 10–12 21 32 33. Further research is needed to explore other dimension-specific effects of social relationships on multimorbidity, such as the qualitative dimension (eg, intimacy), structure dimension (eg, quantity) and function dimension (eg, emotional and practical support), which were not addressed in this study.…”
Section: Discussionsupporting
confidence: 59%
“…6 The associations between the structural (eg, social network size and marital status) and functional (eg, received and perceived social support and loneliness) aspects of social relationships and cognitive performance, morbidity and mortality have been estimated in many studies and populations 6 7 15 ; however, the role of qualitative indicators (eg, subjective rating of satisfaction or quality) is largely unknown. Furthermore, most previous studies have examined only individual types of social relationship satisfaction or quality (eg, satisfaction with the partner, family members, friends, work and social activities), [16][17][18][19][20][21] not considering the relative importance and combined effects of these types in relation to the development of individual chronic conditions and accumulation of multimorbidity. To examine the relative importance of each social relationship type, it is important to compare the associations between individual relationship types and the development of multimorbidity using the same analytical model.…”
Section: What This Study Addsmentioning
confidence: 99%
“…In doing so, each indicator is more distinctly represented. Further, in contrast to the conventional variable-centered approach that assumes relations among predictor variables (e.g., types of activities) and between predictor and outcome variables (e.g., depression) to be uniform within a given population (e.g., Isaac et al, 2009; Ryu et al, 2023), the person-centered approach operates with the assumption that subgroups exist and relations among these variables may differ across subgroups (Bauer, 2022; Daljeet et al, 2017; Korhonen et al, 2014). In other words, the person-centered approach complements traditional variable-centered approaches by identifying how a multidimensional construct may be configured differently across subgroups (different magnitudes of strength along distinct construct dimensions) and relate differently to outcome variables of interest (e.g., high group activity and low religious activity vs. low group activity and high religious activity on depression; Daljeet et al, 2017).…”
Section: Quantifying Patterns Of Activity Engagementmentioning
confidence: 99%
“…However, despite these promising results, several issues in the activity engagement literature require clarification. To wit, although the nature of activity engagement is multidimensional, it is often operationalized as a unidimensional construct (e.g., Ryu et al, 2023). Even when assessed on multiple dimensions, an activity engagement index is sometimes derived by aggregating scores across distinct domains of activities (e.g., Isaac et al, 2009; Merema, 2014).…”
mentioning
confidence: 99%
“…Social activities not only promote mental health but also provide opportunities for older people to socialise and interact with others, enhancing their overall quality of life (Adams et al., 2011). Conversely, studies have shown that a lack of social activities is associated with an increased risk of depression among older people (Ryu et al., 2021).…”
Section: Introductionmentioning
confidence: 99%